Development of e-Comic Science Interactive Learning with Scratch (eCILS) Based on Problem Based Learning to Train Critical Thinking Skills for Junior High School Students (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
This study aims to develop e-comic science interactive learning with scratch (eCILS), to analyze eCILS’ characteristics, test eCILS’ validity, and determine user responses. The research method is development research. The research procedure used is 4D (defined, designed, developed, and disseminated). The research was only up to development due to the pandemic. The result of this research is eCILS. ECILS is an e-comic learning media that have characteristics: (a) equipped with a bibliography, (b) in accordance with problem-based learning syntax, (c) could train critical thinking skills, (d) stories that are displayed in accordance with everyday life, (e) equipped with instructions to use, and (f) in accordance with the characteristics of interactive media learning. ECILS media is very valid to use, this is based on the assessment of material validators who get an average score of 95.63% and media validators 94.38%. Response students to the media are very good indicated by the results of the questionnaire responses of students who get an average of 82.15%. Based on this, it can be concluded that eCILS media can be used as a medium to train critical thinking skills.